Sonorous memory of Pereira (2019)
This article, gives an account of a research processabout the sonorous memory of Pereira state of theart, while attempting to stablish the importance ofcreating a digital record library that preserves thecity’s sounds. In order to reach that objective, thenext procedure has been traced: first, to stablish anapproach to the sonorous memory definitions, and, ina second phase, to make a quantitative study througha poll that inquires about the need of having a publicdigital phonotech, through which community canaccess freely to its contents via Internet. This toolis applied to scholars, historians, and journalists whoare, -at first hand-, the target, and who were -in anoverwhelming majority-, clear in manifesting theimportance of having such a site that categorizesand classifies the existing sounds in the history ofPereira. Finally, it is important to note that, withinthe framework of this process, an agreement todesign and co-produce the digital recording librarywas reached, among the Fundación Universitaria delÁrea Andina and the Emisora Cultural de PereiraRemigio Antonio Cañarte.